Razvoj standarda kombiniranega poučevanja v Sloveniji (University of Maribor Press, 2025)
Development of the Blended Learning Standard in Slovenia. The monograph "Development of the Blended Learning Standard in Slovenia" addresses the modern challenges of digitalization in higher education, particularly in the context of lifelong learning and rapid societal changes. The first chapter explores the evolution of e-learning and clarifies terminological inconsistencies that hinder its effective implementation. The second chapter presents a proposed blended learning standard based on international guidelines, incorporating pedagogical-didactic and organizational aspects. The third chapter focuses on the implementation of this standard in educational practice, while the fourth outlines a normative framework at both the institutional and national levels. Throughout the monograph, the authors build upon the results of the CRP V5-2273 project, offering a systematic analysis of the use of ICT in the Slovenian higher education system. This monograph is a valuable contribution to the understanding and development of high-quality blended learning in Slovenia.